Strenuous Acute Exercise Induces Slow and Fast Twitch-Dependent NADPH Oxidase Expression in Rat Skeletal Muscle - Juliana Osório Alves; Leonardo Matta Pereira; Igor Cabral Coutinho do Rêgo Monteiro; Luiz Henrique Pontes dos Santos; Alex Soares Marreiros Ferraz; Adriano Cesar Carneiro Loureiro; Crystianne Calado Lima; José Henrique Leal-Cardoso; Denise Pires Carvalho; Rodrigo Soares Fortunato; Vânia Marilande Ceccatto (MDPI AG, 2020)
The enzymatic complex Nicotinamide Adenine Dinucleotide Phosphate (NADPH) oxidase (NOx) may be the principal source of reactive oxygen species (ROS). The NOX2 and NOX4 isoforms are tissue-dependent and are differentially expressed in slow-twitch fibers (type I fibers) and fast-twitch fibers (type II fibers) of skeletal muscle, making them different markers of ROS metabolism induced by physical exercise. The aim of this study was to investigate NOx signaling, as a non-adaptive and non-cumulative response, in the predominant fiber types of rat skeletal muscles 24 h after one strenuous treadmill exercise session. The levels of mRNA, reduced glycogen, thiol content, NOx, superoxide dismutase, catalase, glutathione peroxidase activity, and PPARGC1α and SLC2A4 gene expression were measured in the white gastrocnemius (WG) portion, the red gastrocnemius (RG) portion, and the soleus muscle (SOL). NOx activity showed higher values in the SOL muscle compared to the RG and WG portions. The same was true of the NOX2 and NOX4 mRNA levels, antioxidant enzymatic activities, glycogen content. Twenty-four hours after the strenuous exercise session, NOx expression increased in slow-twitch oxidative fibers. The acute strenuous exercise condition showed an attenuation of oxidative stress and an upregulation of antioxidant activity through PPARGC1α gene activity, antioxidant defense adaptations, and differential gene expression according to the predominant fiber type. The most prominent location of detoxification (indicated by NOX4 activation) in the slow-twitch oxidative SOL muscle was the mitochondria, while the fast-twitch oxidative RG portion showed a more cytosolic location. Glycolytic metabolism in the WG portion suggested possible NOX2/NOX4 non-regulation, indicating other possible ROS regulation pathways.